2018
DOI: 10.1111/opo.12582
|View full text |Cite
|
Sign up to set email alerts
|

Vision and academic performance in primary school children

Abstract: Performance on the horizontal and vertical DEM subtests was most strongly associated with academic performance. These data, in conjunction with other clinical data, can provide useful information to clinicians regarding their prescribing and management philosophy for children with lower levels of uncorrected refractive error and binocular vision anomalies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 40 publications
3
38
1
1
Order By: Relevance
“…), which potentially explains the findings of studies that have shown that the DEM ratio is poorly associated with academic outcomes (Wood et al. ). The amount of experience in reading is also likely to be a factor in a child's ability to perform well on the DEM test (reading aloud and across a page) as well as on the PAT‐R.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…), which potentially explains the findings of studies that have shown that the DEM ratio is poorly associated with academic outcomes (Wood et al. ). The amount of experience in reading is also likely to be a factor in a child's ability to perform well on the DEM test (reading aloud and across a page) as well as on the PAT‐R.…”
Section: Discussionmentioning
confidence: 98%
“…While these studies have evaluated RAN and reading ability, few studies have investigated the association between RAN and other academic domains, such as spelling (Scarborough ; Wood et al. ) and mathematics (Wood et al. ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations